UMPSA Contingent Adds Festivity to Independence Day Parade and Procession - Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2023)
KUANTAN, 31 August 2023 - Two contingents from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) participated in the Parade and Procession of the 66th Independence Day Celebration at the State Level for Pahang in 2023, held simultaneously in the districts of Kuantan and Pekan.